(untitled) (Medico Legal Update, 2020)
Makassar City is one of the coastal areas that are vulnerable to the transmission of pulmonary Tuberculosis (TB). The condition of population density in the area can increase the risk of transmission. The aims of the study to determine the risk factors for the occurrence of pulmonary TB in the coastal area of Makassar city. The Design study is case control. Cases are pulmonary TB patients recorded in the medical record of Kaluku Bodoa Health Center. Control is TB suspects who have experienced symptoms of a cough more than 2 weeks and do not have positive TB. The number of samples is 120 with details of 60 cases and 60 controls. Data analysis was used by bivariate and multivariate with odds ratio & logistic regression tests. The results showed that occupancy density (OR: 2.33; 95% CI: 1.103-4.935) and TB contact (OR: 9.077; 95% CI: 1.098-75.02) were risk factors for pulmonary TB, while poor families (OR : 1.909; 95% CI: 0.811- 4.493) and smoking behavior (OR: 1.336; 95% CI: 0.463-3.856) is not a risk factor for the incidence of Pulmonary TB. The conclusion in this study is the probability of the occurrence of pulmonary TB in subjects whose home density is <10 m2 / person and has a contact history with pulmonary TB patients, which is 92%. For Suggestions need health promotion for coastal communities regarding healthy life behavior (PHBS) and ways to reduce the risk of pulmonary TB transmission